Developing a Structural Model of Pain Perception based on Early Maladaptive Schemata Mediated by Cognitive Emotion Regulation in people with Chronic Pain - Mona Abbasi; Hayede Saberi; Afsaneh Taheri (Iranian Evolutionary Educational Psychology Journal, 2023)
Chronic pain affects the type of thinking, function and feeling of the individual and causes various limitations in the person's life.  This study aimed at developing a structural model of pain perception based on early maladaptive schemata mediated by emotion regulation in people with chronic pain. Method: The research method was descriptive correlation and the statistical population included all patients who referred to pain clinics in Tehran in 2020 from which 300 people (175 females and 125 males) were selected by convenience sampling method. They responded to the Granfsky and Craig (2006) Cognitive Emotion Regulation Questionnaires, Young's Early maladaptive Schema (1991), and the Visual Pain Scale. The research data were analyzed by structural equation modelling and hierarchical regression analysis. Findings showed that 1) Direct path coefficient between maladaptive schema and negative (β =0.559) and positive (β =-0.333) emotion regulation strategies was significant (P<.01). 2) The direct path coefficient between the maladaptive schema and pain perception was significant (P<.01). 3) The direct path coefficient between negative emotion regulation strategies and pain perception (β =0.107) was not significant (P>0.5), but the direct path coefficient between positive strategies for negative emotion regulation and pain perception (β =-0.115) was significant (P<.05). It was also found that the moderating role of gender in the relationship between negative and positive emotion regulation strategies with pain perception was not significant (P>.05. 4) The indirect path coefficient between maladaptive schemata and pain perception in patients with chronic pain was significant (β =.098,P<.01).   Conclusion: People's tendency to use positive or negative cognitive emotion regulation strategies can be a determining factor in the relationship between maladaptive schemata and chronic pain perception.